Black girls must be magic : a novel - Allen, Jayne, 1978- (Allen, Jayne, 1978- Black girls must die exhausted, 2022)
"Discovering she's pregnant--after she was told she may not be able to have biological children--Tabitha throws herself headfirst into the world of "single mothers by choice." When an unexpected turn of events draws Marc--her on and off-again ex-boyfriend--back into her world with surprising demands, and the situation at work begins to threaten her livelihood and her identity, Tabitha must make some tough decisions. It takes a village to raise a child, and Tabitha turns to the women who have always been there for her. Will she harness the bravery, strength, and self-love she'll need to keep "the village" together, find her voice at work, and settle things with Marc before the baby arrives?"--